Pengaruh media sosial terhadap kesehatan mental remaja: Studi kasus kesehatan mental siswa SMAN di Bandung - Almaida, Lina (Maliki Interdisciplinary Journal, 2025)
The increasing use of social media over the past two decades has had a significant impact on mental health, especially for young people. This study aims to examine the influence of social media on the mental health of students at one of the senior high schools in Bandung. Using quantitative research method and explanatory research technique, 304 students were selected through purposive sampling technique. The results of linear regression analysis showed that social media use was positively correlated with increased feelings of stress, depression, and anxiety. It is important to be careful when using social media to prevent negative impacts on mental health. It was found that 53% of students had mental health conditions that fell into the moderate category. The implications of this study highlight the importance of caution in using social media to prevent negative impacts on mental health.